Evaluation of platelet indices in patients with acute coronary syndrome and chronic stable angina - Chowdekar, Vijay Sai; Peddi, Naveen (International Journal of Research in Medical Sciences, 2020)
Background: The objective of the study was to evaluate the levels of platelet indices mean platelet volume (MPV) and platelet distribution width (PDW) in patients with acute coronary syndrome (ACS) and chronic stable angina (CSA) and to study its correlation with the occurrence of disease. Methods: This was a hospital-based, case-control, prospective observational study which included 333 patients who fulfilled inclusion and exclusion criteria. All the patients were divided into three groups after clinical investigations: i) 100 patients in ACS group, ii) 114 patients in CSA group and iii) 119 patients in control group. MPV and PDW levels were estimated in all the patients along with other routine investigations related to coronary artery disease. All the data were analyzed using independent sample t-test, ANOVA and Pearson correlation at 95% level of significance. Results: Troponin levels were significantly higher in ACS group compared to CSA and control group (p<0.0001). Mean MPV levels in ACS (15.57±2.11 fL) and CSA (11.27±1.7 fL) groups were significantly higher (p<0.0001) compared with controls (10.48±1.49 fL). A significant elevation in MPV levels was observed in patients with a greater number of diseased vessels. However, no statistically significant correlation was found between PDW and number of diseased vessels (p=0.246). Conclusions: The study concludes that MPV should be considered as an effective tool in predicting the magnitude of acute events in patients with coronary artery disease. However, larger studies with morphological and functional estimation of platelet indices are required to prove this.